Cooperation of a Reductant and an Oxidant in One Pot To Synthesize Amides from Nitroarenes and Aldehydes - Sheng, Guozhu; Wu, Xia; Cai, Xiuhua; Zhang, Wei (Synthesis, 2015)
The reductant zinc powder and the oxidant sodium chlorate were used together in an appropriate ratio in one pot under ambient conditions, to provide an environmentally friendly, effective, and convenient method for the synthesis of aromatic amides in good yields from nitroarenes and aldehydes in the green solvents alcohol and water under atmospheric conditions. The good results indicate that reductants and oxidants with opposing properties can not only be used together without any adverse effects, but also improve the reaction yield through their cooperation.
Keywords: nitroarenes; aldehydes; amides; synthetic methods; one pot